Development of an oral gut-targeted rabies virus-like particles (RVLPs) vaccine with mucosal immune adjuvant LTB via delivering of localized-release microparticles - Jinping Niu; Zhangting Zhao; Tong Zhang; Qingwei Liu; Liyao Huang; Shipo Li; Haipeng Liu; Shaowen Yu; Linfeng Li; Hao Jia; Wenyun Zheng; Feng Yang; et al. (Emerging Microbes and Infections)
Rabies, a fatal zoonotic infectious diseases caused by rabies virus (RABV) infection, still has a high incidence with no effective cure in many Asian countries, even though numerous commercial vaccines have been administered for decades. One of the most important reasons is the neglected that main reservoirs of RABV, such as many stray and wild animals, are inaccessible for effective vaccination, especially in natural wilderness environments. In this study, we developed a highly effective gut-targeted oral rabies vaccine (ORV), which containing the immunoadjuvant LTB by targeted administration of microparticles with local release in the intestine. Based on the virus like particles (RVLPs) were assembled by RABV glycoprotein (RVGP) and matrix protein (RVMP), the enterically released microparticles ELPGA MPs loaded with RVLPs and djuvant LTB (RVLPs + LTB/EPLGA MPs) were prepared and demonstrated the ability of intestinal targeting which released in a pH-dependent manner. Subsequently, in vivo immunoassay experiments showed that the levels of anti-RVLPs IgG, IFN-γ and IL-4 were significantly higher in the RVLPs + LTB/EPLGA MPs groups than in the normal saline group or positive control group (R group) after intragastric administration. Moreover, higher levels of CD4+/CD8+ T cells ratios in the peripheral blood and sIgA in the intestines and feces of mice indicated that RVLPs + LTB/EPLGA MPs group elicited a stronger cellular immune response and mucosal immunity. In short, the novel oral vaccine is exploring valuable strategies of oral gut-targeted vaccines and promising to effectively prevent the spread of RABV among terrestrial carnivorous animals and human populations.